ANALYSIS OF LAMINAR FORCED CONVECTION INSIDE A SQUARE VENTILATED CAVITY USING THE OPENFOAM® - Mioralli, P. C.; Scalon, V. L.; Avallone, E.; Verdério Jr, S. A. (Revista de Engenharia Térmica, 2017)
Laminar forced convection inside a square cavity with inlet and outlet ports was numerically analyzed. The positions of the inlet and outlet ports were fixed and the ports sizes were equal 25% of the side wall. The influence of the Reynolds and Prandtl numbers on the flow and temperature fields inside the cavity was verified for nine cases, with Re = 50, 100 and 500 and Pr = 0.7, 3 and 5. The heat transfer process in the cavity was analyzed from obtained values for the average Nusselt number and the local Nusselt number on the walls. The open source computer package OpenFOAM® was used for simulations considering a two-dimensional flow. For all tested Prandtl numbers, there is a growth in the rotating vortex regions as Reynolds number is increases. The temperature fields are directly related to the presence of the rotating vortices and the temperature gradient is more noticeable at the interface sections of the throughflow stream with the neighboring vortices and the next to the walls for greater Reynolds and Prandtl numbers. It was verified that the local Nusselt number on the walls varies radically with minimum and maximum points and it is dependent on the flow and temperature fields adjacent to the respective wall. The results for average Nusselt number per wall indicated that the bottom wall is the most susceptible to variations in its average Nusselt number and that the top wall present higher values of this parameter for all tested cases. Finally, the average Nusselt number was increased with increasing the Reynolds and Prandtl numbers indicating the enhanced thermal exchange.